Steven Forde, The Ambition to Rule. Alcibiades and the Politics of Imperialism in Thucydides. Itaca (Nueva York) y Londres. Cornell Uníversity Press. 1989, 216 Pp. - FoRNís VAQUERO, César (Gerión. Revista de Historia Antigua, 1992)
Sin resumen